The identity of Maladera infuscata (Moser, 1915), with description of a new species from Taiwan (Coleoptera: Scarabaeidae: Sericini) - Ahrens, Dirk (Zootaxa, 2003)
During a revision of type material of Asian Sericini, the identity of Maladera infuscata (Moser, 1915) was clarified and the following new synonymies were established: Maladera infuscata (Moser, 1915) (= Autoserica koreana Moser, 1919 syn. n.; Aserica okamotoi Murayama, 1938 syn. n.). Taiwanese specimens formerly identified as Maladera infuscata belong to a hitherto undescribed species described herein as Maladera howdeni sp. n.